ENGLISH TEACHER TEACHING STYLE ANALYSIS - Sulviana Sulviana; Muhammad Chairil Imran; Nurain Ali (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2023)
The aim of this study was to ascertain the following: (1) Which teaching styles are employed to enhance students' English proficiency? (2) Determine the students' perspectives on the instructional methods employed by eighth-grade instructors at SMPN 30 Makassar. The investigation was conducted at SMPN 30 Makassar. The design of this study was qualitative analysis. The research population comprised eighth-graders from SMPN 30 Makassar. There are 397 students enrolled in the eighth grade in total. This study's sample consists of ten students and three instructors. The data were gathered through interviews, observations, and documentation by the researcher. (1) According to the findings of the study, students' English proficiency could be enhanced to a greater extent by instructors employing The Total Physical Response (TPR). (2) The eighth-grade students' perceptions of their teachers' teaching styles are as follows: they prefer active teaching styles in the classroom; they prefer games because they can play while learning; it provides fun and enjoyment in the learning process; and they believe that the Total Physical Response (TPR) is a teaching style that can improve their ability to speak English.